PELAKSANAAN HAK MENGAJUKAN RANCANGAN PERATURAN DAERAH OLEH DEWAN PERWAKILAN RAKYAT DAERAH KOTA JAMBI (Studi Kasus DPRD Periode 2009-2014) - Herma Yanti; Said Abdullah (Universitas Batanghari Jambi, 2014)
Based on Law Number 32 of 2004 power up in the hands of regional regulations DPRD. Therefore ask the right plan district regulations also serve as the first right of legislative members. Previously these rights is the right of the Parliament in the institutional, so difficult for the Parliament in the implementation of the resulting DPRD never use rights. Right to file a plan with the rules and made the right district councilors, in order to better facilitate its implementation so hopefully more district plan rules derived from the authority of the Parliament as to form district regulations. As representatives of the people in the area expected to be able to channel the aspirations of the community, represented by the restructuring plan is more oriented district regulations on the protection and enhancement of the welfare of society.keyword : Rights filed Ranperda and DPRD